ANALISIS PERAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN PROFESIONALITAS GURU - Tamim Mulloh; Abd. Qadir Muslim (Journal Publicuho, 2022)
This paper aims to understand how educational supervision is to increase teacher professionalism and how efforts can be made to improve teacher professionalism. This paper uses a qualitative method with analysis from various literature studies. Data analysis techniques according to Miles Huberman and Sandana (2014). The results of the study prove that the impact of educational supervision has an effect on improving the quality of teacher professionalism. In addition, the principal also plays an important role in the professional improvement of teachers. Principals must be able to be good consultants for teachers by providing assistance in solving problems or difficulties experienced by teachers. To increase teacher professionalism, a school principal is also expected to be able to provide input that can help teachers.